Analisis penerapan manajemen strategi pada bank syariah untuk meningkatkan daya saing di era digital - Sabil, Bahri - (Maliki Interdisciplinary Journal, 2025)
The rapid advancement of digital technology requires Islamic banks to adapt strategically to maintain and enhance customer loyalty. This study aims to analyze how the integration of modern technology with Sharia principles can strengthen the competitiveness of Islamic banks in the digital era. A qualitative-descriptive approach was used, examining various digital innovations, such as mobile banking, Sharia-based digital platforms, and blockchain technology, and their impact on customer satisfaction and trust. The study results indicate that the implementation of digital technology can improve efficiency, convenience, and accessibility of services without compromising compliance with Sharia values. Furthermore, digital marketing strategies play a crucial role in expanding the reach of Islamic banks, particularly among the tech-savvy younger generation. Factors such as service quality, consistency of Sharia principles, and product innovation contribute to strengthening customer trust and loyalty. In conclusion, the synergy between digital innovation and Sharia values ​​is key to building a competitive, sustainable, and customer-satisfaction-oriented Islamic banking system.